Physiological and Pathophysiological Implications of Synaptic Tau. (April 2017) - Regan, Philip; Whitcomb, Daniel J.; Cho, Kwangwook
Tauopathies encompass a broad range of neurodegenerative diseases featuring extensive neuronal death and cognitive decline. However, research over the past 30 years has failed to significantly advance our understanding of how tau causes dementia, limiting the design of rational therapeutics. It has become evident that we need to expand our understanding of tau in physiology, in order to delineate how tau may contribute to pathology. This review discusses recent evidence that has uncovered a novel aspect of tau function, based on its previously uncharacterized localization to the synapse. Here, multiple streams of evidence support a critical role for synaptic tau in the regulation of synapse physiology. In particular, long-term depression, a form of synaptic weakening, is dependent on the presence of tau in hippocampal neurons. The regulation of tau by specific phosphorylation events downstream of GSK-3β activation appears to be integral to this signaling role. We also describe how the regulation of synapse physiology by tau and its phosphorylation may inform our understanding of tauopathies and comorbid diseases. This work should provide a platform for future tau biology research in addition to therapeutic design.